Our first goal, any time we have variables in our exponents, is to get the bases the same on both sides of the equation.
Look first at 75^y. 75 is the same as 5*5*3, so let's make it 5^5 * 5^y * 3^y. Combining the 5's gives us 5^2y. Our entire term is now 3^y * 5^2y.
27 is the same as 3^3, so we can adjust this term to become 3^(6y+3)
Now, we have 3^y * 5^2y * 3^(6y+3) on the left.
Combine the 3's and we have 3^(7y+3) * 5^2y
At this point, our bases are the same on both sides, so we know that
2y=4, which means y=2
7y+3 = x
Since we know that y=2, we know 7y+3 is 17, and that x=17.
Hope this helps!